Laboratory Animals: Unification of Legislation in Europe - Rozemond, H. (WBI Studies Repository, 1982)
A committee of experts within the Council of Europe is currently making preparations for a European convention on the protection of laboratory animals. The committee has been designated as the Comite Ad Hoc pour Ia Protection des Animaux (CAHPA). The Council of Europe, the sponsoring organization, is an institution whose chief goal is the peaceful cooperation of most European countries concerning cultural, economic, and social affairs; expressly excluded are matters of military concern. The countries represented on the Council include Austria, Belgium, Cyprus, Denmark, the Federal Republic of Germany, France, Greec:e, Great Britain, Iceland, Ireland, Italy, Liechtenstein, Luxemburg, Malta, the Netherlands, Norway, Spain, Turkey, Sweden, and Switzerland. As part of its work, the Council holds conventions on various topics of broad human interest. Some of the most important documents produced by its conventions have included the Treaty of Rome (Convention for the Protection of Human Rights and Fundamental Freedoms, 1950) and the European Social Charter (1960).